Regulation of melanocortin 1 receptor in allergic rhinitis in vitro and in vivo. Issue 8 (15th June 2016) - Kleiner, S.; Braunstahl, G‐J.; Rüdrich, U.; Gehring, M.; Eiz‐Vesper, B.; Luger, T. A.; Steelant, B.; Seys, S. F.; Kapp, A.; Böhm, M.; Hellings, P. W.; Raap, U.
Abstract: Background: α‐melanocyte‐stimulating hormone (α‐MSH) was shown to inhibit allergic airway inflammation and exert suppressive effects on human basophils. Objective: This study aims to extend our current knowledge on the melanocortin 1 receptor (MC1R) expression in nasal tissue of patients with allergic rhinitis (AR) and functional effects of α‐MSH in human basophils especially from patients with allergic rhinitis. Methods: MC1R expression before and after nasal allergen provocation was studied in nasal mucosal tissue of AR patients and in a mouse model of allergic airway inflammation using immunofluorescence. In vitro regulation of the MC1R and CD203c surface expression on whole‐blood basophils of patients with AR and controls was assessed with flow cytometry. Functional effects of α‐MSH on isolated basophils were analysed regarding apoptosis with flow cytometry and chemotaxis using a Boyden chamber assay. Results: We detected an accumulation of MC1R‐positive basophils in nasal mucosa tissue of patients with AR 24 h after nasal allergen provocation. Such accumulation was not present in mucosa sections from healthy controls. In mice with allergic airway inflammation, we found a clear accumulation of MC1R‐positive basophils in the nasal tissue compared to control mice. MC1R expression was inducible in AR patients and controls by stimulation with anti‐IgE. α‐MSH inhibited anti‐IgE and grass pollen induced upregulation of CD203c, but had no effect on chemotaxis or apoptosis of basophils in vitro . Conclusions and Clinical Relevance: MC1R‐positive basophils accumulate in the nasal mucosa of patients with AR after nasal allergen provocation. Since α‐MSH suppresses proinflammatory effector functions in human basophils via the MC1R, it constitutes an interesting novel target for modulating the allergic inflammatory response.